Strategi Pelatihan dan Pengembangan Guru di Era Kecerdasan Buatan (AI) untuk Optimalisasi Sumber Daya Manusia - Adawiyah, Roviatul Adawiyah; Rindaningsih, Ida (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2024)
Advances in technology, especially artificial intelligence (AI), have dramatically changed the field of education. Teachers now not only teach, but also help students use technology to enhance their learning. This study examines methods of training and developing teachers to adapt to the AI era and optimize HR in schools. The main problems faced by teachers are limited infrastructure, their inability to use technology, and lack of pedagogical understanding of the application of AI. Therefore, teachers should be educated about artificial intelligence tools, new pedagogical methodologies, and the value of lifelong learning. This study found that, in addition to the flexibility and adaptability required to improve interaction and personalize learning, the use of AI is also necessary for effective training. In addition, the successful use of AI in schools also depends on the collaboration between technology and pedagogy and adequate infrastructure support. It is expected that properly trained teachers can utilize AI to create more effective and interactive learning experiences, improve the quality of education, and produce human resources who are ready to face the challenges of the digital era.